A critical analysis of the law of the child act, 2009 on the protection of children against sexual violence - Kweka, Deckrine Dominic (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the award of the Degree of Master of Laws (LLM) in Constitutional and Administrative law of Mzumbe University.